THE EFFECT OF THE IMPLEMENTATION OF PROJECT BASED LEARNING LEARNING MODEL ON ELECTROLYTE AND NON ELECTROLYTE SOLUTION MATERIALS ON THE LEARNING OUTCOMES OF CLASS X MIPA SMA) - Herfirah Nella (International Journal Labs, 2022)
The learning outcomes of class X students at SMA Negeri 1 X Koto Diatas in learning chemistry are still low. One of the methods used to improve student learning outcomes is to apply the Project Based learning model. This study aims to determine the effect of implementing the Project Based Learning model on electrolyte and non-electrolyte solution material on the learning outcomes of students in class X MIPA SMA. This quasi-experimental study used a non-equivalent control group design. The population of this study were all students of class X MIPA even semester of SMAN 1 X Koto Diatas. The sample was taken using a saturated sampling technique, so that class X MIPA 1 was chosen as the experimental class and class X MIPA 2 was the control class. Research data comes from one domain, namely cognitive. The assessment instrument is in the form of a learning outcome test. The data obtained were analyzed using the N-Gain Test, Normality Test, Homogeneity Test and t Test. The results of the study in the cognitive domain obtained that the experimental class average was higher than the control class with the t statistical test, obtained tcount = 1.73 and ttable = 0.25. Thus, it can be concluded that the learning outcomes of students in class X MIPA SMA Negeri 1 X Koto Diatas are affected by the application of the Project Based Learning model on electrolyte and non-electrolyte solution materials.